Faktor-Faktor yang Menentukan Perencanaan Pensiun pada Generasi Sandwich - Ferdian Hadika Prastya; Umi Widyastuti; M. Edo Suryawan Siregar (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
This study aims to analyze the influence of financial literacy, financial behavior, and future orientation on retirement planning among the sandwich generation. Using a quantitative approach with Structural Equation Modeling (SEM) AMOS, the research reveals that financial literacy significantly affects financial behavior, which in turn positively impacts retirement planning. However, future orientation does not show a significant effect on retirement planning, indicating that thinking about the future does not necessarily translate into concrete actions for retirement preparation. Additionally, the findings indicate that financial behavior does not significantly mediate the relationship between financial literacy and retirement planning. These results emphasize the importance of enhancing financial literacy to support better retirement planning, but also suggest that other factors may be necessary to strengthen this relationship.